Multifunctional drug carrier on the basis of 3d–4f Fe/La-MOFs for drug delivery and dual-mode imaging. Issue 42 (8th October 2019) - Lin, Caixue; Chi, Bin; Xu, Chen; Zhang, Cheng; Tian, Feng; Xu, Zushun; Li, Ling; Whittaker, Andrew K.; Wang, Jing
Abstract : Multifunctional drug carriers for simultaneous imaging and drug delivery have emerged as an important new direction for the treatment of cancer. Abstract : Multifunctional drug carriers for simultaneous imaging and drug delivery have emerged as an important new direction for the treatment of cancer. In this study, 3d–4f heterometallic Fe/La-MOFs, with excellent fluorescence and superior positive magnetic resonance imaging with high resolution, were synthesized successfully. The feasibility of Fe/La-MOFs for use in multifunctional drug delivery was demonstrated using doxorubicin hydrochloride (DOX) as the drug model. After modification with tunable amino modified silica layers, the drug loading increased to 150.2 mg g −1 from 23.9 mg g −1, and the pH responsive drug release climbed 80% from 10% upon regulating the pH from 5.8 to 7.4. T 2 -Weighted magnetic resonance imaging (MRI) and fluorescence optical imaging (FOI) both showed a clear concentration-dependent contrast enhancement, indicating potential application as a MRI/FOI dual mode imaging agent. In addition, the FOI of 4T1 cells loaded with Fe/La-MOFs demonstrated their capacity for imaging living cells. The particles were tracked by MRI, and the transverse relativity ( r 2 ) ranks among the highest reported for Fe 3+ complexes (100.49 mM −1 s −1 ). In summary, this is the first report on 3d–4f MOF particles displaying pH-responsive delivery and MRI/FOI dual mode imaging.